MANAGEMENT RISIKO FUNDRAISING PADA PROYEK PEMBANGUNAN KELAS (STUDI KASUS : PONDOK MODERN KURIR LANGIT) - Handayani, Dwi; Ibnurizq, Muhammad Isnanda; Bahar, Ferialdy Idhar; Hanafi, Rosmalina (Center for Study and Journal Management FTI UMI, 2025)
Inventory control problems are crucial issues often faced by heavy equipment distributors that provide various types of spare parts and supporting components. Inaccuracy in managing the availability of goods can hamper after-sales service, which ultimately reduces customer satisfaction levels. Conversely, excess inventory has the potential to cause wasteful storage costs, stockpiling, and increased risk of damage or obsolescence of goods. This study aims to evaluate the inventory control system implemented by the company through the ABC classification approach, considering the determination of safety stock and the application of reorder points as part of the inventory optimization strategy. The results of the analysis show that the application of the ABC classification method can increase the accuracy of demand estimates by up to 84%, which has a positive impact on increasing the company's profitability. However, safety stock management still shows weaknesses, especially in the fast-moving goods category, where the inventory level approaches zero. This condition has the potential to cause delays in delivery to consumers. Therefore, a review and improvement of inventory control policies are needed to ensure the continuity of service and the overall operational efficiency of the company.